Brief intervention for hazardous and harmful drinkers in the emergency department. - D'Onofrio, Gail; Pantalon, Michael V; Degutis, Linda C; Fiellin, David A; Busch, Susan H; Chawarski, Marek C; Owens, Patricia H; O'Connor, Patrick G (Annals of emergency medicine, 2008)
To determine the efficacy of emergency practitioner-performed brief intervention for hazardous/harmful drinkers in reducing alcohol consumption and negative consequences in an emergency department (ED) setting.
Keywords: Adult; Alcohol Drinking; Emergency Service, Hospital; Female; Humans; Intervention Studies; Logistic Models; Male; Mass Screening; Motivation; Outcome and Process Assessment (Health Care); Referral and Consultation; Treatment Outcome